Flash 5 : graphics, animation, and interactivity - Mohler, James L. (OnWord P. New YorkUS, 2000)
Briefly discusses global issues surrounding Flash 5, and website development in general. Explains how to use Flash 5 in conjunction with other graphics programmes. Provides step-by-step instructions for creating stimulating content by, for exampple, integrating sound with visual data; using the drawing and painting tools; and incorporating cel and key frame animations. Includes hands-on exercises throughout; chapter summaries, and glossary.